Social Implications of the Teachings of Gautam Buddha: A Critical Study: Gautam Boudha Ki Shikshaon Ka Samajik Nihitarth: Ek Samikshatmak Adhyayan - Amrit Anurag (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2017)
The origin of Buddhism is seen in opposition to Brahmanism. In such a situation, the social implication of Buddhism is very important. Because where Buddhism rejected caste-based social and ethnic classification, it opened the doors of the Buddhist Sangha for all sections of society. As a result, social coordination got strengthened. But one problem remained that some parts of Brahmin religion and customs and traditions still survived, due to which the social implications of Gautama Buddha's teachings started to be questioned. Through this article, an attempt has been made to look at these facts in a critical manner.